2008
DOI: 10.1143/apex.1.011701
|View full text |Cite
|
Sign up to set email alerts
|

Superconductor-based Light Emitting Diode: Demonstration of Role of Cooper Pairs in Radiative Recombination Processes

Abstract: A light emitting diode with superconducting Nb electrodes was fabricated to investigate the contribution of cooper pairs to radiative recombination in a semiconductor. Electroluminescence observed from the active layer in which electron cooper pairs and normal holes are injected was drastically enhanced at the temperature lower than the superconducting transition temperature of the Nb electrodes. This is the first experimental evidence that cooper pairs enhance radiative recombinations by the superradiance eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 9 publications
5
39
2
Order By: Relevance
“…We have proposed superconductor-based QD-light-emitting diode (SQLED) [1] as the key device to connect the two research fields. Recently Hayashi et al [2] reported the drastic enhancement of LED light output with superconducting effect with Nb electrode deposited n-type InGaAs/InGaAs/p-type InP quantum well (QW) structure. In this sample the luminescence with photo-excitation under zero bias and with current injection were enhanced below the critical temperature of Nb superconducting critical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed superconductor-based QD-light-emitting diode (SQLED) [1] as the key device to connect the two research fields. Recently Hayashi et al [2] reported the drastic enhancement of LED light output with superconducting effect with Nb electrode deposited n-type InGaAs/InGaAs/p-type InP quantum well (QW) structure. In this sample the luminescence with photo-excitation under zero bias and with current injection were enhanced below the critical temperature of Nb superconducting critical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of the samples is that the previous SC-LEDs were grown on (001) InP substrate with metalorganic chemical vapor deposition (MOCVD), while the present sample was grown on (311)B InP substrate with MBE. The other difference is that most of the previous SC-LEDs were doped n-type up to 5 Â 10 18 cm À3 , 11,14 while the present sample was doped 1 Â 10 18 cm À3 . In principle, the higher electron concentration extends the coherence length as discussed in Section II, but the higher impurity concentration may increase the scattering probability.…”
Section: Discussionmentioning
confidence: 61%
“…The luminescence intensity shows sharp increase below T C of 9.07 K. This well reproduces our previous observation of luminescence enhancement in SC-LEDs. 11,13 Above T C the decay time constant remains the same, but below T C it shows clear decrease with temperature. This also well reproduces our previous observation of decrease of the electroluminescence decay time constant in SC-LEDs.…”
Section: Time-resolved Luminescence Measurementsmentioning
confidence: 90%
See 2 more Smart Citations